Pengaruh Self-Efficacy, Coaching dan Empowerment Terhadap Kinerja Karyawan CV. Laxita Paramitha Semarang (Studi pada Mahasiswa S1 Universitas Diponegoro) - Salsabila Adissa Maharani; Widiartanto Widiartanto (Universitas Diponegoro, 2017)
So far, unstable employee performance has been a problem for both small and largecompanies. One of the factors that affect the stability of performance is the level of selfefficacyowned by employees. By knowing how much employee confidence, it will be easierfor companies to develop performance improvement strategies. Therefore, the research wasconducted with the aim to find out how big the influence of self-efficacy, coaching andempowerment on employee performance on CV. Laxita Paramitha Semarang.Type of research used is eksplanatory research, with the samples of 43 respondentsusing saturated sampling approach. Data collection using questionnaire with Likertmeasurement scale. Data analysis method used is validity and reliability test, multiple linearregression test, classical assumption test, regression test, coefficient of determination(Adjusted R Square), significance of t test and F test, and cross tabulation. The resultsindicate that the variables of self-efficacy, coaching and empowerment each have asignificant and positive influence on employee performance.From the test results known for self-efficacy variable has a coefficient ofdetermination of 29.3% and T variable test of self-efficacy equal to t count 4,287> t table2,0195. Coefficient of determination for coaching variable equal to 68% and T variable testof coaching equal to t count 2,025> t table 2,0195. The coefficient of determination forempowerment variable is 30.3% and Test t empowerment variable t count 4.338> t table2.0195. Test F of F arithmetic 11,010> F table 3.2317 and free from the classicalassumption.The conclusion in this research is self-efficacy is the factor that most influence thework performance in the company, the application of good coaching and the willingness ofmanagement in giving empowerment. There is a positive and significant influence between allindependent variables on the dependent variable, either partially or simultaneously. As forsuggestions for the company is to pay more attention to employee competence, periodicevaluation of supervisor performance and better dialogue between management andemployees.